2011
DOI: 10.1007/s00467-011-1916-8
|View full text |Cite
|
Sign up to set email alerts
|

Change in left ventricular geometry during antihypertensive treatment in children with primary hypertension

Abstract: The pattern of the left ventricle (LV) has important significance in adults with hypertension. The aim of the present study was to analyze changes and determinants of LV geometry after 1 year of antihypertensive treatment in children with primary hypertension (PH) in relation to metabolic abnormalities and anthropometrical parameters. In 86 children (14.1 ± 2.4 years) with newly diagnosed PH, LV geometry and biochemical parameters before and after 12 months of standard antihypertensive therapy were assessed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
3
24
0
1
Order By: Relevance
“…Our study also demonstrated an increase in left ventricular mass and a higher likelihood of development of abnormal left ventricular geometry in children who had essential hypertension; eccentric hypertrophy being the most prevalent type of abnormal geometry (35). According to the literature in children, a high incidence of concentric hypertrophy is seen in the obese and hypertensive children (12, 36) and it is also the type that is less likely to regress (35).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our study also demonstrated an increase in left ventricular mass and a higher likelihood of development of abnormal left ventricular geometry in children who had essential hypertension; eccentric hypertrophy being the most prevalent type of abnormal geometry (35). According to the literature in children, a high incidence of concentric hypertrophy is seen in the obese and hypertensive children (12, 36) and it is also the type that is less likely to regress (35).…”
Section: Discussionsupporting
confidence: 61%
“…According to the literature in children, a high incidence of concentric hypertrophy is seen in the obese and hypertensive children (12, 36) and it is also the type that is less likely to regress (35). Left ventricular hypertrophy is the most commonly assessed marker of target organ damage in hypertensive children with a prevalence of 10% to 38% (6, 7, 11, 36-41) and is a significant independent predictor of diastolic dysfunction in children with essential hypertension (14).…”
Section: Discussionmentioning
confidence: 99%
“…Children with hypertension associated with obesity have the highest prevalence of cardiac geometry alterations, in particular, a great prevalence of both concentric and eccentric hypertrophy has been observed [20,52,57]. Moreover, Śladowska-Kozłowska et al [58] observed that eccentric hypertrophy was the most frequent pattern of left ventricular remodeling in adolescents with essential hypertension and central obesity. A greater prevalence of abnormal cardiac geometry was observed in prehypertensive and hypertensive adolescents, as compared to the normotensive ones, without an effect of weight [10,43].…”
Section: Discussionmentioning
confidence: 96%
“…Increased LVMI is defined as an increase in the mass of the left ventricle, which can be secondary to an increase in wall thickness, an increase in cavity size, or both. This increase in mass predominantly results from a chronic increase in the afterload of the left ventricle caused by hypertension and/or by chronic volume load (23)(24)(25). Aortic annulus diameter enlargement has been reported in children with hypertension other than Turner and Marfan syndromes (26,27).…”
Section: Discussionmentioning
confidence: 99%